Efektivitas Penggunaan Model Pembelajaran Problem Based Instruction (PBI) Dalam Meningkatkan Hasil Belajar Siswa - Muhamad Zaril Gapari (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2023)
The quality of human resources is closely related to the quality of education, from basic education to higher education. The pace of development of science and technology today has had a huge influence or impact on the field of education and teaching. This research aims to determine the effectiveness of using the Problem-Based Instruction (PBI) learning model in improving student learning outcomes in class 3 economics subjects at SMPN 2 Jerowaru. The method used in this research is the experimental method. The research design used was a non-equivalent pretest-posttest control group. The population in this study were all 3rd grade students at SMPN 2 Jerowaru, totaling 2 classes, namely class III1, and III2. The sampling technique used was cluster random sampling, and those selected as samples were class III2 as the experimental class and III1 as the control class. Meanwhile, the data analysis test was carried out using the chi-square data normality test, and the data homogeneity test using the Bartlet test, while the hypothesis testing technique used was parametric statistical analysis, namely the t-test. After data analysis was carried out, the average value of the experimental group was obtained. 73.83 and the control group 57.83. This means that the use of the Problem-Based Instruction Model can improve the quality of solving the questions given, while from the results of hypothesis testing it is obtained ???? ℎi???????????? g > ???? ????????????????????, namely 20.21 > 1.6948. This means that the proposed hypothesis is accepted (Ho is rejected and Ha is accepted), meaning that the problem-based instruction learning model is effective in improving student learning outcomes in class 3 economics subjects at SMPN 2 Jerowaru.